2015
DOI: 10.1902/jop.2015.150074
|View full text |Cite
|
Sign up to set email alerts
|

Keratinized Gingiva Height Increases After Alveolar Corticotomy and Augmentation Bone Grafting

Abstract: Orthodontic therapy combined with alveolar decortication and augmentation bone grafting resulted in a significant increase in KT height. Although KT height surrounding the dentition has been devalued by evidence-based studies, the value-added protection of KT height increase after decortication and augmentation bone grafting offsets the concerns of orthodontic proclination or expanding mandibular incisors facially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 42 publications
4
58
0
Order By: Relevance
“…Six studies investigated bone grafting with CAOT and two studies performed free gingival grafts prior to orthodontic treatment. Most of the studies of interest were limited to mandibular anterior teeth …”
Section: Focused Clinical Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies investigated bone grafting with CAOT and two studies performed free gingival grafts prior to orthodontic treatment. Most of the studies of interest were limited to mandibular anterior teeth …”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…PhMT can contribute to maintain or increase the thickness of facial bone in order to withstand orthodontic tooth movement, especially in cases of mandibular decompensation PhMT can potentially expand the limits of tooth movement, especially mandibular incisors PhMT with CAOT may maintain or slightly increase the width of keratinized tissue …”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…There was no statistically significant difference between the CAOT with or without PhMT‐b . No studies evaluated gingival thickness (GT), only one article reported an average increase of 0.78 mm KTW after PhMT‐b versus a loss of 0.38 mm KTW with no PhMT‐b …”
Section: Resultsmentioning
confidence: 97%
“…In terms of the treatment time duration, only two cohort studies reported CAOT and PhMT‐b reduced treatment time from 22 months (conventional orthodontic treatment) to 7 months; and 10.9 months (pre‐orthognathic surgery treatment time) to 8.7 months . Other studies described accelerated orthodontic tooth movement but failed to provide direct comparison data between CAOT and conventional orthodontic treatment, Two studies reported similar treatment time with a mean of 15 to 17 weeks with or without PhMT‐b, indicating that the accelerated tooth movement is primarily a result of the corticotomy injury itself and the creation of a transient demineralized bone matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation